Food diversity of the Tapanuli Orangutan (Pongo tapanuliensis) in the Tapanuli Orangutan Research Station Plan, North Sumatra, Indonesia - Arief, Harnios; Mijiarto, Joko (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The Tapanuli orangutan (Pongo tapanuliensis) is found only in the Tapanuli area. This species includes protected and endangered animals and has a very limited distribution. An important component of animal management is feed availability. This study aims to assess the diversity of food in the Tapanuli orangutan at the Tapanuli Research Station Plan, Batu Satail, Sipirok District. Research was carried out in November 2021 by conducting a vegetation analysis on 3 predetermined paths. The results showed that in this area, there were 91 plant species from 42 families, of which 29 species (31.87%) were orangutan food. However, the highest plant importance index value is dominated by nonfood plants.